The effects of magnetic field (MFs) on in vitro culture of human umbilical cord derived mesenchymal stem cells (hUC-MSCs) - Abdul Hamid, Haslinda (2018)
The potential hazardous effects of magnetic field (MF) exposures on individual have been extensively studied. However, a number of studies have surprisingly observed that response to optimal MF has significantly increased the proliferation rate of stem cells. Accordingly, this current study aims to investigate the potential impact of induced Static Magnetic Field (SMF) on human Umbilical Cord-Derived Mesenchymal Stem Cells (hUC-MSCs) using Samarium Cobalt (SmCo5). SmCo5 was selected for the study due to its known strong permanent moment magnetization, and stable against the influence of demagnetization. The 10,000 of hUC-MSCs at passage 3, seeding in 60 mm petri dish were grown in constant ‘direct exposure’ (DE) of 21.6 mT SMF, alongside with ‘indirect exposure’ (IE) and ‘negative control’ (NC) groups. The growth kinetic experiments in the current study exhibited exponential growth at day four in the DE group, compared to day six for both IE and NC groups. Population doubling time (PDT) was also performed and the results showed DE group contributed significantly to the change in PDT for a period of passage 3 with p<0.05. Cell cycle analysis after 18 hours revealed that DE group entered to the cell cycle at higher percentage where hUC-MSCs exposed with MF was committed into 55.18 % cells in S phase and 21.75 % cells at G2/M phase compared to IE. ([3H]-TdR) revealed that DE group gave the highest proliferation capability at all points of seeding density, when compared to IE and NC groups. In addition, flow cytometer analysis discovered no significant difference in the expression of the surface markers of DE group compared to IE and NC. SMF also was observed to have the potential to induce higher expression of pluripotency-associated markers (OCT4, SOX2, NANOG, and REX1) in DE group than in the IE and NC groups as analyzed via RT-PCR. In conclusion, through MF exposure, small quantity of collected MSCs could be expanded rapidly in a short period of time. This finding may suggest MF as a new modality to expand MSC for various therapeutic applications.